THE VARIATION OF THERMAL CONDUCTIVITY WITHIN LIMESTONE COMPLEXES IN SELECTED OUTCROPS OF NORTHWESTERN PENINSULAR MALAYSIA - BINTI ABD KADER, SITI NORLIANA (Universiti Teknologi PETRONAS, 2015)
This project is in an initiative taken to understand the heat flow of limestone formation since there are inadequate studies of thermal conductivity on limestone formation especially in Northwestern Peninsular Malaysia. General geology of selected outcrops in Langkawi, Perlis and Simpang Pulai, Perak were studied and samples were taken for laboratory analysis such as thin sections, thermal conductivity, mercury porosity, density, total carbon, scanning electron microscopy (SEM) and x-ray diffraction (XRD). Limestone outcrops of Setul Formation in Perlis and Langkawi showed a variety of facies consisting of mudstone, crystalline, grainstone and dolomitic limestone. The formation have undergone diagenetic processes such as cementation, dolomitization and stylolitization. Limestone outcrops of Kinta Valley in Simpang Pulai consist of mudstone and crystalline limestone. A huge part of the outcrop is crystalline and forms an interlocking crystal of calcite which reflect the effect of metamorphism on the area. In the Setul Formation, the presence of ooids, piloids, pisoids and some possible fossil fragments reflect that the sediments were deposited in lagoon environment. As for the limestone in Kinta Valley, eventhough there is no evidence to indicate the original depositional environment, based on earlier published work, it is believed that Kinta Valley limestone is part of slope facies environment. As a variety of facies are present, comparison of thermal conductivity (k) showed that the k values range from 1.3 to 3.6 W/mK. The result is greatly affected by the minerals and clay content, porosity, density, metamorphism and diagenetic processes acted upon the formation.